A clinical guide to the management of genitourinary symptoms in breast cancer survivors on endocrine therapy. (April 2017) - Sousa, Mariana S.; Peate, Michelle; Jarvis, Sherin; Hickey, Martha; Friedlander, Michael
There is increasing attention and concern about managing the adverse effects of adjuvant endocrine therapy for women with early breast cancer as the side effects of therapy influence compliance and can impair quality of life (QoL). Most side effects associated with tamoxifen (TAM) and aromatase inhibitors (AIs) are directly related to estrogen deprivation, and the symptoms are similar to those experienced during natural menopause but appear to be more severe than that seen in the general population. Prolonged estrogen deprivation may lead to atrophy of the vulva, vagina, lower urinary tract and supporting pelvic structures, resulting in a range of genitourinary symptoms that can in turn lead to pain, discomfort, impairment of sexual function and negatively impact on multiple domains of QoL. The genitourinary side effects may be prevented, reduced and managed in most cases but this requires early recognition and appropriate treatment. We provide an overview of practical clinical approaches to understanding the pathophysiology and the management of genitourinary symptoms in postmenopausal women receiving adjuvant endocrine therapy for breast cancer.